Diagonal Quadratic Approximation for Decentralized Collaborative TSO+DSO Optimal Power Flow - Mohammadi, Ali; Mehrtash, Mahdi; Kargarian, Amin (IEEE transactions on smart grid, 2019)
Collaborative operation of electricity transmission and distribution systems improves the economy and reliability of the entire power system. However, this is a challenging problem given that transmission system operators (TSOs) and distribution system operators (DSOs) are autonomous entities that are unwilling to reveal their commercially sensitive information. This paper presents a decentralized decision-making algorithm for collaborative TSO+DSO optimal power flow (OPF) implementation. The proposed algorithm is based on analytical target cascading for multilevel hierarchical optimization in complex engineering systems. A local OPF is formulated for each TSO/DSO taking into consideration interactions between the transmission and distribution systems while respecting autonomy and information privacy of TSO and DSOs. The local OPF of TSO is solved in the upper-level of hierarchy, and the local OPFs of DSOs are handled in the lower-level. A diagonal quadratic approximation (DQA) and a truncated DQA are presented to develop iterative coordination strategies in which all local OPFs are solved in a parallel manner with no need for a central coordinator. This parallel implementation significantly enhances computations efficiency of the algorithm. The proposed collaborative TSO+DSO OPF is evaluated using a 6-bus and the IEEE 118-bus test systems, and promising results are obtained.